Humans and technology in the Anthropocene: Six rules. (August 2014) - Haff, Peter
Humans play an essential role in creating the technological systems of the Anthropocene, but, nonetheless, large-scale technology – the 'technosphere' – operates according to a quasi-autonomous dynamics, summarized by six rules: (1) the rule of inaccessibility, that large components of the technosphere cannot directly influence the behavior of their human parts; (2) the rule of impotence, that most humans cannot significantly influence the behavior of large technological systems; (3) the rule of control, that a human cannot control a technological system that expresses a larger number of behaviors than he himself; (4) the rule of reciprocity, that a human can interact directly only with systems his own size; (5) the rule of performance, that most humans must perform at least some tasks that support the metabolism of the technosphere; and (6) the rule of provision, that the technosphere must provide an environment for most humans conducive to their survival and function.